2010
DOI: 10.4236/eng.2010.211115
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation of Single Phase Core Type Transformer Using Bacterial Foraging Algorithm

Abstract: The electrical circuit equivalents of magnetic device structures such as transformer require an exact knowledge of its parameters. Efficient parameter estimation technique is essential to obtain the equivalent circuit parameters of transformer because the parameters are used to manipulate parasitic elements and to obtain the enhanced circuit performance. In this paper, Bacterial Foraging Algorithm (BFA) has been applied to estimate the equivalent circuit parameters of single phase core type transformer. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 14 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…Besides, precise calibration of these professional instruments is also needed, which complicates the measurement process. Reference [21] proposed using numerical algorithms to achieve parameter extraction and parameter identification of the transformer. Besides, some numerical methods for transformer evaluation in [9,22] have been proposed to design wire-wound transformers.…”
Section: Previous Evaluation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, precise calibration of these professional instruments is also needed, which complicates the measurement process. Reference [21] proposed using numerical algorithms to achieve parameter extraction and parameter identification of the transformer. Besides, some numerical methods for transformer evaluation in [9,22] have been proposed to design wire-wound transformers.…”
Section: Previous Evaluation Methodsmentioning
confidence: 99%
“…From (21), it can be found that the dynamic CM capacitance CQ is not only determined by the structure capacitance C0 and the terminal connection of winding, but also determined by the voltage potential difference Vd between the primary ground and the secondary ground.…”
Section: Selection Of Resistor Rmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, a few different views on transformer parameters estimation can be found in the available literature [6][7][8][9][10][11][12][13][14]. Some of them include transformer's nonlinear behavior [6][7][8], whereas others deal with traditional (Steinmetz) transformer equivalent circuit [9][10][11][12][13][14]. Since transformers and induction machines have similar equivalent circuit, some studies investigate parameter estimation of both induction machine and transformer [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of the optimization techniques, based on the evolutionary algorithms is that the form of the cost (or goal) function can be defined arbitrary. This is reason why these techniques are also very popular for transformer parameters estimation [9][10][11][12][13][14][15][16]. They include Practical Swarm Optimization (PSO) [9,15,16], Genetic Algorithm (GA) [9,13], Imperialist Competitive Algorithm (ICA) [10], Gravitational Search Algorithm (GSA) [10], Bacterial Foraging Algorithm (BFA) [11,12] and Artificial Bee Colony Algorithm (ABCA) [14] and can be applied on transformer nameplate data or on the measured load data, without disconnection of the transformer from the power system.…”
Section: Introductionmentioning
confidence: 99%